Serum IgE Levels Are Associated With the Prognosis of Minimal Change Disease - Li, Heng; Wang, Lefeng; Li, Xiayu; Chen, Wenqing; Zhang, Ying; Chen, Jianghua (Frontiers in Immunology, 2022)
Background: Previous reports showed that some patients with minimal change disease (MCD) had high serum immunoglobulin E (IgE) levels. This study aimed to explore the proportion of MCD patients with high serum IgE levels and evaluate the correlation between serum IgE levels and MCD remission and relapse. Methods: This study enrolled 222 new-onset patients with renal biopsy-confirmed MCD from October 2012 to October 2019 at the First Affiliated Hospital of Zhejiang University in Hangzhou, China. Patients’ demographics and clinical parameters were analyzed. Results: The results indicated that 70.3% of 222 MCD patients had high serum IgE levels (IgE > 100.0 IU/mL). Moreover, 134 patients were treated with glucocorticoids alone and divided into the low- and high-IgE groups, according to the median serum IgE level (523.5 IU/mL). The mean time to complete remission of the low- and high-groups was 29.0 ± 2.2 and 45.7 ± 4.2 days, respectively (log-rank test; P = 0.002). The mean time to total remission was 19.1 ± 1.4 and 31.6 ± 3.2 days of the low- and high-IgE groups, respectively (log-rank test; P < 0.001). The mean time to first relapse in the low- and high-IgE groups was 701.2 ± 65.0 and 425.0 ± 52.6 days, respectively (log-rank test; P = 0.002). Serum IgE ≥ 523.5 IU/mL was an independent correlation factor affecting the patients’ remission and relapse. Conclusion: Serum IgE level was an independent correlation factor for MCD remission and relapse. MCD patients with high serum IgE levels were prone to delayed remissions and early relapses.